Comparative genomic analysis of Bacillus atrophaeus HAB-5 reveals genes associated with antimicrobial and plant growth-promoting activities - Dahar, Ghulam Yaseen; Wang, Huan Wei; Rajer, Faheem Uddin; Jin, Pengfie; Xu, Peidong; Abro, Manzoor Ali; Qureshi, Abdul Sattar; Karim, Asad; Miao, Weiguo (Frontiers in Microbiology, 2024)
Bacillus atrophaeus HAB-5 is a plant growth-promoting rhizobacterium (PGPR) that exhibits several biotechnological traits, such as enhancing plant growth, colonizing the rhizosphere, and engaging in biocontrol activities. In this study, we conducted whole-genome sequencing of B. atrophaeus HAB-5 using the single-molecule real-time (SMRT) sequencing platform by Pacific Biosciences (PacBio) (USA), which has a circular chromosome with a total length of 4,083,597 bp and a G+C content of 44.21%. The comparative genomic analysis of B. atrophaeus HAB-5 with other strains, B. amyloliquefaciens DSM7, B. atrophaeus SRCM101359, B. velezensis FZB42, B. velezensis HAB-2, and B. subtilis 168, revealed that these strains share 2465 CDSs, while 599 CDSs are exclusive to the B. atrophaeus HAB-5 strain. Many gene clusters in the B.atrophaeus HAB-5 genome are associated with the production of antimicrobial lipopeptides and polypeptides. These gene clusters comprised of distinct enzymes that encode three Nrps, two Pks, one terpene, one lanthipeptide, one T3PKS, one Ripp, and one thiopeptide. In addition to the likely IAA-producing genes (trpA, trpB, trpC, trpD, trpE, trpS, ywkB, miaA, and nadE), there are probable genes that produce volatile chemicals (acoA, acoB, acoR, acuB, and acuC).Moreover, HAB-5 contained genes linked to iron transportation (fbpA, fetB, feuC, feuB, feuA, fecD), sulfur metabolism (cysC, sat, cysK, cysS, sulP), phosphorus solubilization (ispH, pstA, pstC, pstS, pstB, gltP, phoH), and nitrogen fixation (nif3-like, gltP, gltX, glnR, glnA, nadR, nirB, nirD, nasD, narl, narH, narJ, and nark). In conclusion, this study provides a comprehensive genomic analysis of B. atrophaeus HAB-5, pinpointing the genes and genomic regions linked to the antimicrobial properties of the strain. These findings advance our knowledge of the genetic basis of the antimicrobial properties of B. atrophaeus and imply that HAB-5 may employ a variety of commercial biopesticides and biofertilizers as a substitute strategy to increase agricultural output and manage a variety of plant diseases.